DEVELOPMENT OF NON –DESTRUCIVE TESTING (NDT) TECHNOLOGY IN PAKISTAN - Khan, Asghar Ali (The Nucleus, 2020)
Non-Destructive Testing (NDT) techniques are being extensively used to improve and maintain the quality of manufactured goods as well as for proper maintenance of industrial plants and equipment. Typical industries that benefit most include Aerospace, Chemical, Heavy Mechanical Fabrication, Conventional and Nuclear Power Generation, Automobiles, Oil and Gas, Shipbuilding, Foundries, and Armaments, etc. As the name implies, with these techniques an industrial product is inspected mostly for defects in its structure without destroying it. Among the most widely used NDT techniques for the detection of internal defects are Radiographic and Ultrasonic Testing. For surface and just below the surface defects Magnetic Particle Testing, Penetrant Testing and Eddy Current Testing are commonly used. In addition to these, there are some NDT methods which have specific applications. These include Acoustic Emission, Thermal and Infrared Testing, Microwave Testing, Computer Tomography, Strain Gauging, Leak Testing and Holography, etc. This paper describes various phases through which the development of NDT technology passed and its present state of the art. It started with the undertaking of a nuclear technology programme and has matured along with it. As it stands we are fully competent to undertake various essential activities related to this technology, namely, (i) Training and certification of NDT personnel at various levels. (ii) Provision of NDT services to various industrial sectors including nuclear power during manufacture, fabrication, pre-service inspection (PSI) and in-service inspection (ISI).